Qualitative analysis of participant experiences during an ecological momentary assessment study of nonsuicidal self-injury among veterans. (April 2022) - Gromatsky, Molly; Patel, Tapan A.; Wilson, Sarah M.; Mann, Adam J.; Aho, Natalie; Carpenter, Vickie L.; Calhoun, Patrick S.; Beckham, Jean C.; Goodman, Marianne; Kimbrel, Nathan A.
Highlights: Nonsuicidal self-injury (NSSI) is a prevalent predictor of veteran suicide. Ecological momentary assessment (EMA) is valuable for the study of veteran NSSI. Veterans with NSSI qualitatively evaluated an EMA protocol for NSSI/suicide. Emotional/social benefits of participating were described, including NSSI reduction. Challenges/recommendations were largely tech-related and easy to implement. Abstract: Ecological momentary assessment (EMA) is a useful tool to investigate antecedents and consequences of nonsuicidal self-injury (NSSI), a robust predictor of Veteran suicide risk. Despite elucidating temporal changes among dynamic variables, EMA remains underutilized to study NSSI among veterans, perhaps due to concerns of safety and utility. The present study analyzed data collected from semi-structured interviews of veterans following a 28-day EMA study of NSSI, including benefits, challenges, and recommendations for improvement. Participants included 34 veterans endorsing NSSI history, most meeting criteria for NSSI Disorder. Qualitative analysis of de-identified transcripts used the rigorous and accelerated data reduction (RADaR) technique and thematic analysis. Findings revealed all veterans reported at least one emotional/social benefit to participation, including finding it therapeutic, gaining self-awareness/insight, and improved social functioning. Challenges and recommendations were primarily technology-related, including adjustment to device use. Many expressed interest in incorporation of clinical resources, use of personal devices/VA app, and ability to share responses with providers. Assessment frequency/content was never described as triggering suicidal/nonsuicidal urges and over half of participants noted urge/behavior reduction. Results support acceptability and safety of EMA for NSSI among veterans and potential clinical utility as a psychotherapy adjunct to promote self-awareness and NSSI reduction.